Beneath the crust of culture : psychoanalytic anthropology and the cultural unconscious in American life - Stein, Howard F. (Contemporary psychoanalytic studies, 2004)
In this book, the author presents a pioneering interpretation of culture as constituting a dynamic relationship between the visible "crust" and the elusive "core" of social life. He meticulously maps the role of the unconscious in shaping much of American life in the late 20th and early 21st centuries. He crosses and transcends disciplinary boundaries in studies of September 11, 2001, the 1999 Columbine High School massacre, the execution of Timothy McVeigh, the 1995 Oklahoma City bombing, the 1999 Worcester, Massachusetts fire, and the eruption of hypernationalism and xenophobia in nations and workplaces - all as cultural phenomena with a psychodynamic core. He shows how the experience of loss in the face of massive social change often leads to equally massive defence against the experience of mourning. Beneath the Crust of Culture will be of interest not only for behavioural and social science professionals, but also for a lay public interested in understandings of culture deeper than the surface of the news and of official pronouncements